Insight into the WNT system and its drug related response - S. Tamanini; L. Idolazzi; D. Gatti; O. Viapiana; A. Fassio; M. Rossini (PAGEPress Publications, 2013)
The WNT signalling pathway is a complex system for transferring information for DNA expression from the cell surface receptors to cytoplasm and then to the nucleus. It is based on several proteins that work together as agonists and antagonists in order to maintain homeostasys and to promote anabolic processes. The WNT system acts on all cellular lines involved in bone resorption and formation. WNT pathway can mainly be triggered by two different signalling cascades. The first is well known and is the so-called WNT-beta catenin system (or the canonical pathway), the second is known as the non canonical WNT pathway. WNT proteins form a superfamily of secreted glycoproteins. The association with surface receptors, called Frizzled, that are members of the G protein-coupled receptors superfamily and co receptors like low-density lipoprotein receptor-related proteins 5 and 6 (LRP5/6) complete the WNT system. LRP5/6 show high affinity for WNT antagonists that modulate the activity of this pathway: DKK1 and sclerostin (SCL), that play a crucial role in modulating the WNT system. The WNT-pathway and in particular its antagonists SCL and DKK1 seems to play a key role in the regulation of bone remodeling during treatment with bone active agents such as bisphosphonates, but not only. Their effects become relevant especially in the course of long-term treatments.